THE RELATIONSHIP BETWEEN EDUCATIONAL BACKGROUND OF FUND MANAGERS AND EQUITY FUNDS PERFORMANCE IN INDONESIA - Arsyirawati (NIM 19014057), Rida
Indonesia is one of the developing countries its good condition to increase GDP through investing in the capital market, and this is a great opportunity for the Government to add theincome from society in Indonesia. Investment is one way for individuals to maximize their wealth and earn more profit from investment instrument. For small investors who do not have enough data about financial asset investment and the lack of ability to manage the fund that will be invested can use financial intermediaries. Financial asset investment is an activity to increase the wealth through investment instrument which consists of the money market, bond, and capital market. A mutual fund is one of the financial intermediaries that provide services to help manage the funds belonging to an investor who will be handled by the investment manager.Investment managers have an important role in mutual funds to manage the assets of investor into investment instruments and ensure that assets that have a higher value in the future. The success of investment manager can be seen from the performance of mutual fund through the return and the risk that accrue the investor. The higher rate of return is, the higher the risk will be. Investment manager also serves to set up a portfolio of investor asset with an excellent and efficient strategy to provide a diversified portfolio that affects the amount of return were obtained by investors. In addition to investors, investment manager will get the fee of the return obtained investors in accordance with the services provided. Every mutual fund has a different level of management fee following the policies of the company. The performance of mutual funds can be influenced by several factors from both the characteristics of funds and also the characteristics of an investment manager. This research examines the relationship between the performance of equity mutual fund and fund manager characteristics in Indonesia. The characteristic researched is education background of investment manager which is divided into three criteria there are education level, international graduation, and holder of the professional certificate such as CFA, CAIA, FRM (financial advisory). Methods for measuring the performance of mutual funds use risk-adjusted return method developed by Sharpe (1994) and Treynor (1966) which describe the risk and return of investment management that gives the result of risk-adjusted return. Previous research studies reveal that fund manager characteristics are significantly influenced by fund performance. The data were obtained in this research is 147 of equity mutual fund in Indonesia in period 20142016. Statistics method adopt panel data regression with fixed effect model.These results agree with the previous research that there is a significant correlation between fund performance and fund manager characteristics. The results conclude that there is a significant correlation between education background of fund managers and fund performance. Of the three criteria of education backgrounds, two variables have an impact on the performance of equity mutual fund in Indonesia, namely education level, and financial advisory. An investment manager who graduated from higher education level would give a good performance because the more knowledge they learned it would affect in defining and deciding strategies in investing. It is aligned with the manager who holds professional certifications like CFA, CAIA, FRM, and this shows the professionalism of manager and the special expertise in investment give significant influence on fund performance. Professional certifications also prove that investment manager can forecast the market condition will be helpful the manager in stock selecting and market timing to invest in the capital market.